2019
DOI: 10.1002/ddr.21574
|View full text |Cite
|
Sign up to set email alerts
|

Effect of IS01957, a para‐coumaric acid derivative on pharmacokinetic modulation of diclofenac through oral route for augmented efficacy

Abstract: Diclofenac is one of the world's largest selling nonsteroidal anti‐inflammatory drugs. The major concerns related to oral diclofenac therapy are gastrointestinal and cardiovascular side effects for which explicitly emphasis has been given to use it at lowest effective dose for the shortest duration. On the other hand, IS01957 has been designed under the purview of anti‐inflammatory drug and bioavailability enhancer. IS01957 have dual action on inflammation and nociception with acceptable safety profile. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This is a colorimetric assay to measure the release of inorganic phosphate in the reaction mixture composed of membrane protein, test compound, and ATP. BCRP-dependent ATPase activity for safranal (1.25–20 μM) was also performed using human BCRP membrane in the same manner as mentioned in the case of P-gp-dependent ATPase activity except cyclosporine (10 μM) was used as standard . The chemical stability of safranal in SGF and SIF was determined by incubating safranal (500 μM) in the respective fluid for 2 and 4 h, respectively .…”
Section: Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a colorimetric assay to measure the release of inorganic phosphate in the reaction mixture composed of membrane protein, test compound, and ATP. BCRP-dependent ATPase activity for safranal (1.25–20 μM) was also performed using human BCRP membrane in the same manner as mentioned in the case of P-gp-dependent ATPase activity except cyclosporine (10 μM) was used as standard . The chemical stability of safranal in SGF and SIF was determined by incubating safranal (500 μM) in the respective fluid for 2 and 4 h, respectively .…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Safranal concentration in the sample was determined by HPLC (Table ) using a matrix match calibration curve where standards were prepared by spiking a known amount of safranal into blank plasma. After that, the obtained plasma concentration data at respective time points were analyzed to determine the pharmacokinetic parameters by PK Solutions software (Summit Research Services) using the noncompartmental method. , …”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, diabetic patients are prone to renal impairment . In this direction, it is well known that a drop or rise in plasma concentration of the drug may lead to therapeutic failure and growing resistance for antibiotics or enhance dose-dependent adverse effects, respectively. …”
Section: Introductionmentioning
confidence: 99%
“…Our earlier discovery p-coumaric acid derivative was found to be suitable for intraperitoneal as well as oral route of administration with good absorption rate in mice plasma [35]. Later study also proved that there was shown improvement in diclofenac action in the presence of IS01957 involving MAPK pathways when associated oral administration [36]. Hence to demonstrate the important factors behind permeation of drug formulations, in-vitro release studies were under taken across the cellophane membrane using a diffusion cell.…”
Section: Fig 1 Types Of Permeation Enhancersmentioning
confidence: 99%